Fixed-income portfolio management in crisis period: Expected tail loss (ETL) approach - Mehdi Mili (Kiel Institute for the World Economy (IfW), 2012)
The purpose of this study is to develop an efficient strategy for managing fixed-income portfolios in crisis periods. We use the volatility ratio model of Briere and Szafarz (2008) and the Expected Tail Loss (ETL) approach of Litzenberger and Modest (2008). Our methodology is applied to U.S. and European markets of fixed-income products using interest rates at different maturities over the period 2002 through 2010. U.S. portfolio exhibits his optimum with small amounts of interest rates belonging to the short-term strategy and the European portfolio exhibits his optimum with small amounts belonging to the long-term strategy. The results show that the ETL is a better measure of the downside risk than the Value-at-Risk (VaR). For instance, the U.S. (European) portfolio has a VaR of -3.6% (-0.7%) against an ETL of -6% (-0.8%). Moreover, we find that, for these two geographical areas, the short-term interest rates make little contribution to the overall ETL of the American fixed-income portfolio and vice versa for the European portfolio.
Keywords: G11; G15; N20; 330; fixed-income portfolio; financial crisis; flight-to-quality; contagion; expected tail loss